ANALISIS PEMBELAJARAN FIKIH BERBASIS PENDIDIKAN MULTIKULTURAL DI MTs DDI KABALLANGAN KABUPATEN PINRANG - Mardia; Muhammad Mukhtar. S; Rohman Rohman (Edu Global : Jurnal Pendidikan Islam, 2022)
Multicultural-based education is seen as important in responding to existing differences. The diversity of schools of law in fiqh and issues of khilafiyah often become internal debates among Muslims and often lead to divisions. This type of research is qualitative research, the data source is through documentation and resource persons, data collection techniques are through observation, documentation, and interviews. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results show that (1) the dimensions of multicultural values ​​in fiqh learning consist of curriculum dimensions, dimensions in teaching materials consist of values ​​of tolerance, equality of rights, values ​​of brotherhood, justice, and social ethics, (2) implementation of multicultural values ​​in comparison of schools in fiqh learning, namely promoting the values ​​of tolerance and not being fanatical, being inclusive, not discriminatory, teaching the background of the emergence of differences, ethics in responding to differences, and promoting the values ​​of peace and unity, (3) the implications of multicultural values in fiqh learning, namely (1) implications in the domain of attitude (affection) which consists of awareness and cultural sensitivity, responsiveness to culture, and skills to avoid conflict, (2) domain of knowledge (cognitive) which consists of knowledge of the language and culture of people others, and the ability to analyze and translate cultural behavior and knowledge about cultural awareness. (3) the learning domain which consists of the ability to correct distortions, stereotypes, and misunderstandings about ethnic groups.